INSTITUTIONAL FRAMEWORK OF INTERACTIONS BETWEEN NATIONAL INNOVATIVE SYSTEMS OF BRICS COUNTRIES - T. Leonova; N. Malanicheva; A. Eygel; A. Malanicheva (Вестник университета)
The current trends of BRICS’ economic developments is described. The arguments proving necessity of transfer to the active development on educational and scientific potential are presented. The modern NSI treatment is given. The NSI concept is presented both in narrow and broad vision. BRICS’ measures aimed at NSI development both individually and in collaboration are described. The recommendations on realization development and collaboration of NSI is given.